A kind of organosilicon antibacterial finishing agent and its preparation process and use method
An organosilicon antibacterial finishing agent was prepared by combining nano-zinc oxide with organosilicon quaternary ammonium salt, which solved the problems of poor heat resistance and easy washing away of antibacterial agents in the prior art, and achieved long-lasting antibacterial effect and good hand feel on natural fiber fabrics.
Patent Information
- Application Number
- CN202411670875.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-21
AI Technical Summary
Existing antibacterial finishing agents have problems such as poor heat resistance, easy washing and removal, and short-lasting antibacterial effect. In particular, when organosilicon quaternary ammonium salt finishing agents are applied to textiles, the softness and fluffiness are reduced, and the antibacterial effect of plant essential oils is limited and easy to be lost.
A pretreated organosilicon quaternary ammonium salt was prepared by combining nano-zinc oxide with organosilicon quaternary ammonium salt and treating it with silver nitrate and hydrogen peroxide. This pretreated organosilicon quaternary ammonium salt was then combined with sodium bentonite and octadecyl dimethyl benzyl ammonium chloride to expand the interlayer spacing and combine it with chitosan to form a stable composite bentonite. This composite was then used to coat an essential oil complex, thus preparing an organosilicon antibacterial finishing agent.
It achieves long-lasting antibacterial properties on natural fiber fabrics, with an antibacterial rate of over 96.4%. It exhibits excellent antibacterial activity against Staphylococcus aureus and Escherichia coli, good washability, and a pleasant hand feel without affecting softness or fluffiness.
Smart Images

Figure CN119145223B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textile finishing agents, and in particular to an organosilicon antibacterial finishing agent and a preparation process and a use method thereof. Background Art
[0002] Natural fibers have the advantages of good air permeability, strong water absorption and no irritation to human skin, so fabrics made of natural fibers are becoming more and more popular. As we all know, there are various bacteria in the environment where humans live. Since natural fiber fabrics have porous and loose structures, they are easy to absorb various impurities and are ideal places for bacteria to parasitize and reproduce. Not only will they cause damage to natural fiber fabrics, but they will also cause various diseases, seriously affecting human health.
[0003] Now, the antibacterial properties of fabrics can be better achieved through antibacterial functional finishing agents. Among the existing antibacterial finishing agents, natural antibacterial agents have poor heat resistance and are easily restricted by production conditions, making them difficult to produce on a large scale; although inorganic antibacterial agents have good heat resistance and durability, they are relatively expensive; and organic antibacterial agents have strong bactericidal power, a relatively fast bactericidal speed, and a low price, but their heat resistance is relatively poor. At the same time, the softness and fluffiness of fabrics treated with antibacterial functional finishing agents are reduced, resulting in a poor hand feel.
[0004] Existing organosilicon quaternary ammonium salt finishing agents are widely used due to the physiological inertness of organosilicon, good durability and extremely low toxicity, but still have the disadvantages of not being washable, easy to wash out and not having long-term antibacterial effect. Although the prior art also discloses the application of plant essential oils in the finishing of textiles, the antibacterial effect is limited, and it is very easy to lose, and the antibacterial time is poor. If organosilicon quaternary ammonium salt type is compounded with plant essential oils for textile finishing, the antibacterial effect can be enhanced, which has excellent research prospects. Summary of the invention
[0005] The purpose of the invention is to solve the shortcomings of the prior art and to propose an organosilicon antibacterial finishing agent and its preparation process and use method.
[0006] A preparation process of an organosilicon antibacterial finishing agent comprises the following steps:
[0007] S1, disperse nano zinc oxide in water and stir evenly, add organosilicon quaternary ammonium salt thereto, stir at 70-80°C for 1-2h, add silver nitrate and stir for 10-20min, add saturated ammonia water and stir for 5-10min, add hydrogen peroxide solution and stir for 1-2h, filter, wash with water, and vacuum dry to obtain pretreated organosilicon quaternary ammonium salt;
[0008] S2, adding sodium bentonite to deionized water and stirring for 10-20 min, adding octadecyl dimethyl benzyl ammonium chloride thereto, stirring at 70-80° C. for 1-2 h, centrifuging, washing, vacuum drying, and sieving to obtain pretreated bentonite;
[0009] S3, dissolving chitosan in an acetic acid aqueous solution and stirring evenly, adding pretreated bentonite, essential oil complex, and emulsifier thereto, stirring at 10-20° C. for 5-15 min, adding dropwise to a sodium tripolyphosphate solution, standing for 1-2 h, filtering, washing with water, cooling to -40 to -20° C., keeping warm for 1-2 h, and freeze-drying to obtain a composite bentonite;
[0010] S4. Mix the composite bentonite, pretreated organosilicon quaternary ammonium salt, emulsifier, penetrant JFC and deionized water, and store at a low temperature of 10-20°C.
[0011] Preferably, in S1, the organosilicon quaternary ammonium salt is octadecyldimethyltrimethylsilylammonium chloride.
[0012] Preferably, in S1, the mass ratio of nano zinc oxide, organosilicon quaternary ammonium salt, silver nitrate, saturated ammonia water and hydrogen peroxide is 1-2:4-8:1-2:1-2:0.2-0.9.
[0013] Preferably, in S2, the mass ratio of sodium bentonite to octadecyl dimethyl benzyl ammonium chloride is 5-10:1-2.
[0014] Preferably, in S3, the mass ratio of chitosan, pretreated bentonite, essential oil complex, emulsifier and sodium tripolyphosphate is 1-2:6-12:1-3:1-2:0.15-0.96.
[0015] Preferably, in S3, the emulsifier is alkylphenol polyoxyethylene ether-10.
[0016] Preferably, in S3, the mass fraction of the sodium tripolyphosphate solution is 0.5-1.2%.
[0017] Preferably, in S3, the essential oil complex comprises, by mass, 3-5 parts of oregano essential oil, 1-2 parts of cinnamon essential oil, 4-8 parts of thyme essential oil, and 4-8 parts of tea tree essential oil.
[0018] Preferably, in S4, the emulsifier is tridecanol polyoxyethylene ether.
[0019] Preferably, in S4, the mass ratio of the composite bentonite, the pretreated organosilicon quaternary ammonium salt, the emulsifier, the penetrant JFC, and the deionized water is 9-20:7-15:1-2:1-2:20-30.
[0020] An organosilicon antibacterial finishing agent is prepared by adopting the preparation process of the organosilicon antibacterial finishing agent.
[0021] The method for using the above-mentioned organosilicon antibacterial finishing agent is as follows: the natural fiber fabric is dipped and rolled in the above-mentioned organosilicon antibacterial finishing agent at a bath ratio of 3-4:1, twice dipped and twice rolled, the roller pressure is 0.05-0.1MPa, and the liquid carrying rate is controlled to be 100%; the fabric is sent into a roller, the pressure in the roller bin is adjusted to 0.1-0.2MPa, maintained for 1-2min, centrifuged to remove the liquid for 1-3min, vacuum dried, washed with water, and fixed at a low temperature of 10-20℃. Beneficial Effects
[0022] The invention hydrolyzes octadecyldimethyltrimethylsilyl ammonium chloride and combines it with the surface hydroxyl group of nano zinc oxide, and then cooperates with silver nitrate to combine the silver ions through coordination bonds, and then loads on the surface to form a pretreated organic silicon quaternary ammonium salt, which not only has excellent antibacterial performance, but also is high temperature resistant and has a significant antistatic effect.
[0023] The invention adopts sodium bentonite and octadecyl dimethyl benzyl ammonium chloride for compounding, and octadecyl dimethyl benzyl ammonium chloride is used for intercalation of sodium bentonite to expand the interlayer distance, thereby promoting full dispersion between sodium bentonite and chitosan, and after solidification, the essential oil composite has excellent coating and adsorption performance and high stability.
[0024] The present invention uses pre-treated organosilicon quaternary ammonium salt and composite bentonite to compound, and the two have excellent affinity and can be firmly combined into the natural fiber structure. It is found through experiments that the fabric treated with the present invention has good antibacterial properties against Staphylococcus aureus up to 96.4%, and antibacterial properties against Escherichia coli up to 98.8%; and in terms of washability, after 50 washes, it still has excellent antibacterial properties against Staphylococcus aureus and Escherichia coli, which can meet the needs of practical applications.
[0025] The invention not only has natural fragrance, but also has antibacterial and bactericidal effects, deodorizing and anti-mite effects, and can maintain lasting washing resistance, has almost no effect on the washing fastness and rubbing fastness of colored fabrics, and has a good hand feel, and can be suitable for human clothing and household textiles. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The figure is a comparison chart of the original antibacterial properties of cotton fabrics treated with the finishing agents obtained in Example 5 and Comparative Examples 1-2 and the antibacterial properties after 50 washes.
[0027] Figure 2 The deodorization rate of cotton fabrics treated with the finishing agents obtained in Example 5 and Comparative Examples 1-2 and the deodorization rate after 50 washes are compared.
[0028] Figure 3 The figures are a comparison of the mite inhibition rates of cotton fabrics treated with the finishing agents obtained in Example 5 and Comparative Examples 1-2 and the mite inhibition rates after 50 washes. DETAILED DESCRIPTION
[0029] The present invention will be further explained below in conjunction with specific embodiments. Example 1
[0030] A preparation process of an organosilicon antibacterial finishing agent comprises the following steps:
[0031] S1. Disperse 1 kg of nano zinc oxide in 30 kg of water and stir evenly, add 4 kg of octadecyldimethyltrimethylsilylammonium chloride, stir at a speed of 100 r / min for 1 h, and the stirring temperature is 70 ° C. Add 1 kg of silver nitrate and stir for 10 min, add 1 kg of saturated ammonia water and stir for 5 min, add 1 kg of 20% hydrogen peroxide solution and stir for 1 h, filter, wash with deionized water, and vacuum dry to obtain the pretreated organosilicon quaternary ammonium salt;
[0032] S2, adding 5 kg of sodium bentonite to 30 kg of deionized water, stirring at 1000 r / min for 10 min, adding 1 kg of octadecyl dimethyl benzyl ammonium chloride thereto, stirring at a temperature of 70° C. for 1 h, centrifuging, washing, vacuum drying, and passing through a 100 mesh sieve to obtain pretreated bentonite;
[0033] S3, dissolving 1kg of chitosan in 5kg of 1% acetic acid aqueous solution, adding 6kg of pretreated bentonite, 1kg of essential oil complex, and 1kg of alkylphenol polyoxyethylene ether-10 thereto, stirring at a temperature of 10°C at a speed of 50r / min for 5min, adding dropwise to 30kg of 0.5% sodium tripolyphosphate solution by mass fraction, standing for 1h, filtering, washing with deionized water, cooling to -40°C, keeping warm for 1h, and freeze-drying to obtain composite bentonite;
[0034] The essential oil complex is composed of oregano essential oil, cinnamon essential oil, thyme essential oil, and tea tree essential oil in a mass ratio of 3:1:4:4;
[0035] S4. Mix 9 kg of composite bentonite, 7 kg of pretreated organosilicon quaternary ammonium salt, 1 kg of tridecanol polyoxyethylene ether, 1 kg of penetrant JFC, and 20 kg of deionized water, stir at a speed of 1000 r / min for 10 min, and store at a low temperature of 10°C. Example 2
[0036] A preparation process of an organosilicon antibacterial finishing agent comprises the following steps:
[0037] S1, 2kg of nano zinc oxide was dispersed in 50kg of water and stirred evenly, 8kg of octadecyldimethyltrimethylsilylammonium chloride was added thereto, stirred at a speed of 500r / min for 2h, the stirring temperature was 80°C, 2kg of silver nitrate was added and stirred for 20min, 2kg of saturated ammonia water was added and stirred for 10min, 3kg of 30% hydrogen peroxide solution was added and stirred for 2h, filtered, washed with deionized water, and vacuum dried to obtain the pretreated organosilicon quaternary ammonium salt;
[0038] S2, adding 10 kg of sodium bentonite to 50 kg of deionized water, stirring at 2000 r / min for 20 min, adding 2 kg of octadecyl dimethyl benzyl ammonium chloride thereto, stirring at 80 ° C for 2 h, centrifuging, washing, vacuum drying, and passing through a 200 mesh sieve to obtain pretreated bentonite;
[0039] S3, dissolving 2kg of chitosan in 10kg of 2% acetic acid aqueous solution, adding 12kg of pretreated bentonite, 3kg of essential oil complex, and 2kg of alkylphenol polyoxyethylene ether-10 thereto, stirring at a temperature of 20°C at a speed of 100r / min for 15min, adding dropwise to 80kg of 1.2% sodium tripolyphosphate solution by mass fraction, standing for 2h, filtering, washing with deionized water, cooling to -20°C, keeping warm for 2h, and freeze-drying to obtain composite bentonite;
[0040] Among them, the essential oil complex is composed of oregano essential oil, cinnamon essential oil, thyme essential oil, and tea tree essential oil in a mass ratio of 5:2:8:8;
[0041] S4. Mix 20 kg of composite bentonite, 15 kg of pretreated organosilicon quaternary ammonium salt, 2 kg of tridecanol polyoxyethylene ether, 2 kg of penetrant JFC, and 30 kg of deionized water, stir at a speed of 3000 r / min for 20 min, and store at a low temperature of 20°C. Example 3
[0042] A preparation process of an organosilicon antibacterial finishing agent comprises the following steps:
[0043] S1, 1.2kg nano zinc oxide was dispersed in 45kg water and stirred evenly, 5kg octadecyldimethyltrimethylsilylammonium chloride was added thereto, stirred at a speed of 400r / min for 80min, the stirring temperature was 77°C, 1.3kg silver nitrate was added and stirred for 18min, 1.3kg saturated ammonia water was added and stirred for 9min, 1.5kg mass fraction of 28% hydrogen peroxide solution was added and stirred for 80min, filtered, washed with deionized water, and vacuum dried to obtain the pretreated organosilicon quaternary ammonium salt;
[0044] S2, adding 9 kg of sodium bentonite to 35 kg of deionized water, stirring at 1800 r / min for 13 min, adding 1.7 kg of octadecyl dimethyl benzyl ammonium chloride thereto, stirring at 73 ° C for 100 min, centrifuging, washing, vacuum drying, and passing through a 150 mesh sieve to obtain pretreated bentonite;
[0045] S3, 1.3kg chitosan was dissolved in 9kg acetic acid aqueous solution with a mass fraction of 1.3%, 10kg pretreated bentonite, 1.5kg essential oil complex, 1.7kg alkylphenol polyoxyethylene ether-10 were added thereto, stirred at a temperature of 12°C at a speed of 90r / min for 8min, added dropwise to 70kg sodium tripolyphosphate solution with a mass fraction of 0.6%, allowed to stand for 100min, filtered, washed with deionized water, cooled to -35°C, kept warm for 100min, and freeze-dried to obtain composite bentonite;
[0046] The essential oil complex is composed of oregano essential oil, cinnamon essential oil, thyme essential oil, and tea tree essential oil in a mass ratio of 3.5:1.8:5:7;
[0047] S4. Mix 12 kg of composite bentonite, 13 kg of pretreated organosilicon quaternary ammonium salt, 1.3 kg of tridecanol polyoxyethylene ether, 1.8 kg of penetrant JFC, and 22 kg of deionized water, stir at a speed of 2500 r / min for 12 min, and store at a low temperature of 18°C. Example 4
[0048] A preparation process of an organosilicon antibacterial finishing agent comprises the following steps:
[0049] S1, 1.8kg nano zinc oxide was dispersed in 35kg water and stirred evenly, 7kg octadecyldimethyltrimethylsilylammonium chloride was added thereto, stirred at a speed of 200r / min for 100min, the stirring temperature was 73°C, 1.7kg silver nitrate was added and stirred for 12min, 1.7kg saturated ammonia water was added and stirred for 7min, 2.5kg hydrogen peroxide solution with a mass fraction of 22% was added and stirred for 100min, filtered, washed with deionized water, and vacuum dried to obtain the pretreated organosilicon quaternary ammonium salt;
[0050] S2, adding 7 kg of sodium bentonite to 45 kg of deionized water, stirring at 1200 r / min for 17 min, adding 1.3 kg of octadecyl dimethyl benzyl ammonium chloride thereto, stirring at a temperature of 77 ° C for 80 min, centrifuging, washing, vacuum drying, and passing through a 150 mesh sieve to obtain pretreated bentonite;
[0051] S3, 1.7kg chitosan was dissolved in 7kg acetic acid aqueous solution with a mass fraction of 1.7%, 8kg pretreated bentonite, 2.5kg essential oil complex, 1.3kg alkylphenol polyoxyethylene ether-10 were added thereto, stirred at a temperature of 18°C at a speed of 70r / min for 12min, added dropwise to 50kg sodium tripolyphosphate solution with a mass fraction of 1%, allowed to stand for 80min, filtered, washed with deionized water, cooled to -25°C, kept warm for 80min, and freeze-dried to obtain composite bentonite;
[0052] Among them, the essential oil complex is composed of oregano essential oil, cinnamon essential oil, thyme essential oil, and tea tree essential oil in a mass ratio of 4.5:1.2:7:5;
[0053] S4, 18kg of composite bentonite, 9kg of pretreated organosilicon quaternary ammonium salt, 1.7kg of tridecanol polyoxyethylene ether, 1.2kg of penetrant JFC, and 28kg of deionized water were mixed, stirred at a speed of 1500r / min for 18min, and stored at a low temperature of 12°C. Example 5
[0054] A preparation process of an organosilicon antibacterial finishing agent comprises the following steps:
[0055] S1, 1.5kg of nano zinc oxide was dispersed in 40kg of water and stirred evenly, 6kg of octadecyldimethyltrimethylsilylammonium chloride was added thereto, stirred at a speed of 300r / min for 90min, the stirring temperature was 75°C, 1.5kg of silver nitrate was added and stirred for 15min, 1.5kg of saturated ammonia water was added and stirred for 8min, 2kg of 25% hydrogen peroxide solution was added and stirred for 90min, filtered, washed with deionized water, and vacuum dried to obtain the pretreated organosilicon quaternary ammonium salt;
[0056] S2, adding 8 kg of sodium bentonite to 40 kg of deionized water, stirring at 1500 r / min for 15 min, adding 1.5 kg of octadecyl dimethyl benzyl ammonium chloride thereto, stirring at a temperature of 75 ° C for 90 min, centrifuging, washing, vacuum drying, and passing through a 150 mesh sieve to obtain pretreated bentonite;
[0057] S3, 1.5kg chitosan was dissolved in 8kg acetic acid aqueous solution with a mass fraction of 1.5%, 9kg pretreated bentonite, 2kg essential oil complex, 1.5kg alkylphenol polyoxyethylene ether-10 were added thereto, stirred at a temperature of 15°C at a speed of 80r / min for 10min, added dropwise to 60kg sodium tripolyphosphate solution with a mass fraction of 0.8%, allowed to stand for 90min, filtered, washed with deionized water, cooled to -30°C, kept warm for 90min, and freeze-dried to obtain composite bentonite;
[0058] Among them, the essential oil complex is composed of oregano essential oil, cinnamon essential oil, thyme essential oil, and tea tree essential oil in a mass ratio of 4:1.5:6:6;
[0059] S4. Mix 15 kg of composite bentonite, 11 kg of pretreated organosilicon quaternary ammonium salt, 1.5 kg of tridecanol polyoxyethylene ether, 1.5 kg of penetrant JFC, and 25 kg of deionized water, stir at a speed of 2000 r / min for 15 min, and store at a low temperature of 15°C.
[0060] Comparative Example 1
[0061] A preparation process of an organosilicon antibacterial finishing agent comprises the following steps:
[0062] S1, stirring 1.5 kg of nano zinc oxide, 6 kg of octadecyldimethyltrimethylsilylammonium chloride, and 1.5 kg of silver nitrate for 15 min to obtain a mixture containing organic silicon quaternary ammonium salt;
[0063] S2, adding 8 kg of sodium bentonite to 40 kg of deionized water, stirring at 1500 r / min for 15 min, adding 1.5 kg of octadecyl dimethyl benzyl ammonium chloride thereto, stirring at a temperature of 75 ° C for 90 min, centrifuging, washing, vacuum drying, and passing through a 150 mesh sieve to obtain pretreated bentonite;
[0064] S3, 1.5kg chitosan was dissolved in 8kg acetic acid aqueous solution with a mass fraction of 1.5%, 9kg pretreated bentonite, 2kg essential oil complex, 1.5kg alkylphenol polyoxyethylene ether-10 were added thereto, stirred at a temperature of 15°C at a speed of 80r / min for 10min, added dropwise to 60kg sodium tripolyphosphate solution with a mass fraction of 0.8%, allowed to stand for 90min, filtered, washed with deionized water, cooled to -30°C, kept warm for 90min, and freeze-dried to obtain composite bentonite;
[0065] Among them, the essential oil complex is composed of oregano essential oil, cinnamon essential oil, thyme essential oil, and tea tree essential oil in a mass ratio of 4:1.5:6:6;
[0066] S4. Mix 15 kg of composite bentonite, 11 kg of a mixture of quaternary ammonium salts containing organic silicon, 1.5 kg of tridecanol polyoxyethylene ether, 1.5 kg of penetrant JFC, and 25 kg of deionized water, stir at a speed of 2000 r / min for 15 min, and store at a low temperature of 15°C.
[0067] Comparative Example 2
[0068] A preparation process of an organosilicon antibacterial finishing agent comprises the following steps:
[0069] S1, 1.5kg of nano zinc oxide was dispersed in 40kg of water and stirred evenly, 6kg of octadecyldimethyltrimethylsilylammonium chloride was added thereto, stirred at a speed of 300r / min for 90min, the stirring temperature was 75°C, 1.5kg of silver nitrate was added and stirred for 15min, 1.5kg of saturated ammonia water was added and stirred for 8min, 2kg of 25% hydrogen peroxide solution was added and stirred for 90min, filtered, washed with deionized water, and vacuum dried to obtain the pretreated organosilicon quaternary ammonium salt;
[0070] S2, 1.5kg chitosan was dissolved in 8kg of 1.5% acetic acid aqueous solution, 9kg sodium bentonite, 2kg essential oil complex, 1.5kg alkylphenol polyoxyethylene ether-10 were added thereto, stirred at 80r / min for 10min at a temperature of 15°C, added dropwise to 60kg of 0.8% sodium tripolyphosphate solution, allowed to stand for 90min, filtered, washed with deionized water, cooled to -30°C, kept warm for 90min, and freeze-dried to obtain composite bentonite;
[0071] Among them, the essential oil complex is composed of oregano essential oil, cinnamon essential oil, thyme essential oil, and tea tree essential oil in a mass ratio of 4:1.5:6:6;
[0072] S3, 15kg of composite bentonite, 11kg of pretreated organosilicon quaternary ammonium salt, 1.5kg of tridecanol polyoxyethylene ether, 1.5kg of penetrant JFC, and 25kg of deionized water were mixed, stirred at a speed of 2000r / min for 15min, and stored at a low temperature of 15°C.
[0073] The cotton fabric was treated with the organosilicon antibacterial finishing agent obtained in Example 5 and Comparative Examples 1-2, specifically as follows: the cotton fabric was immersed in the above finishing liquid at a bath ratio of 3.5:1, twice immersed and twice rolled, the roller pressure was 0.08 MPa, and the liquid carrying rate was controlled to 100%; it was sent into the drum, the pressure in the drum bin was adjusted to 0.15 MPa, maintained for 1.5 minutes, centrifuged to remove the liquid for 2 minutes, vacuum dried, washed with water, and low-temperature shaped at 15°C.
[0074] With reference to GB / T 20944.3-2008 "Evaluation of antimicrobial properties of textiles Part 3: Oscillation method", the antibacterial rate of each group of cotton fabrics after finishing was determined (the test strains were Staphylococcus aureus AATCC6538, Escherichia coli AATCC8739 and Candida albicans AATCC10231). With reference to GB / T 33610.1-2019 "Determination of deodorizing properties of textiles Part 1: General rules", the deodorizing rate of each group of cotton fabrics after finishing was determined. With reference to the inhibition method in GB / T 24253-2009 "Evaluation of anti-mite properties of textiles", the inhibition rate of each group of cotton fabrics after finishing against mites was determined.
[0075] The finished cotton fabric was washed 50 times using a washing color fastness tester and then the antibacterial rate, deodorization rate and mite inhibition rate were measured again.
[0076] like Figures 1 to 3 As shown, after the cotton fabric is finished with the organosilicon antibacterial finishing agent obtained in Example 5, its antibacterial rate, deodorization rate and mite inhibition rate are better than those of Comparative Examples 1-2, and after 50 washes, its antibacterial rate, deodorization rate and mite inhibition rate are much better than those of Comparative Examples 1-2 (P < 0.05).
[0077] The applicant believes that: this is because the present invention combines octadecyl dimethyl trimethyl silyl ammonium chloride with the surface hydroxyl group of nano zinc oxide after hydrolysis, and then cooperates with the effect of silver nitrate, silver ions are combined by coordination bonds, and then loaded on the surface to form pre-treated organosilicon quaternary ammonium salts, which not only have excellent antibacterial properties, but also are resistant to high temperatures and have remarkable antistatic effects. The present invention also adopts sodium bentonite and octadecyl dimethyl benzyl ammonium chloride to compound, octadecyl dimethyl benzyl ammonium chloride is intercalated to sodium bentonite, and the interlayer spacing is expanded, which can promote it to be fully dispersed with chitosan, and then after curing, the essential oil complex is coated with excellent adsorption performance and high stability. The present invention also adopts pre-treated organosilicon quaternary ammonium salts and composite bentonite to compound, and both have excellent affinity and can be firmly combined into the natural fiber structure at the same time.
[0078] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A process for preparing an organosilicon antibacterial finishing agent, characterized in that: The steps include: S1, disperse nano zinc oxide in water and stir evenly, add organosilicon quaternary ammonium salt thereto, stir at 70-80°C for 1-2h, add silver nitrate and stir for 10-20min, add saturated ammonia water and stir for 5-10min, add hydrogen peroxide solution and stir for 1-2h, filter, wash with water, and vacuum dry to obtain pretreated organosilicon quaternary ammonium salt; The organosilicon quaternary ammonium salt is octadecyldimethyltrimethylsilylpropylammonium chloride; S2, adding sodium bentonite to deionized water and stirring for 10-20 min, adding octadecyl dimethyl benzyl ammonium chloride thereto, stirring at 70-80° C. for 1-2 h, centrifuging, washing, vacuum drying, and sieving to obtain pretreated bentonite; S3, dissolving chitosan in an acetic acid aqueous solution and stirring evenly, adding pretreated bentonite, essential oil complex, and emulsifier thereto, stirring at 10-20° C. for 5-15 min, adding dropwise to a sodium tripolyphosphate solution, standing for 1-2 h, filtering, washing with water, cooling to -40 to -20° C., keeping warm for 1-2 h, and freeze-drying to obtain a composite bentonite; The mass ratio of chitosan, pretreated bentonite, essential oil complex, emulsifier and sodium tripolyphosphate is 1-2:6-12:1-3:1-2:0.15-0.96; S4. Mix the composite bentonite, pretreated organosilicon quaternary ammonium salt, emulsifier, penetrant JFC and deionized water, and store at a low temperature of 10-20°C.
2. The preparation process of the organosilicon antibacterial finishing agent according to claim 1, characterized in that: In S1, the mass ratio of nano zinc oxide, organosilicon quaternary ammonium salt, silver nitrate, saturated ammonia water and hydrogen peroxide is 1-2:4-8:1-2:1-2:0.2-0.
9.
3. The preparation process of the organosilicon antibacterial finishing agent according to claim 1, characterized in that: In S2, the mass ratio of sodium bentonite to octadecyl dimethyl benzyl ammonium chloride is 5-10:1-2.
4. The preparation process of the organosilicon antibacterial finishing agent according to claim 1, characterized in that: In S3, the emulsifier is alkylphenol polyoxyethylene ether-10; In S3, the mass fraction of the sodium tripolyphosphate solution is 0.5-1.2%.
5. The preparation process of the organosilicon antibacterial finishing agent according to claim 1, characterized in that: In S3, the essential oil complex comprises, by mass, 3-5 parts of oregano essential oil, 1-2 parts of cinnamon essential oil, 4-8 parts of thyme essential oil, and 4-8 parts of tea tree essential oil.
6. The preparation process of the organosilicon antibacterial finishing agent according to claim 1, characterized in that: In S4, the emulsifier is tridecanol polyoxyethylene ether; In S4, the mass ratio of composite bentonite, pretreated organosilicon quaternary ammonium salt, emulsifier, penetrant JFC, and deionized water is 9-20:7-15:1-2:1-2:20-30.
7. An organosilicon antibacterial finishing agent, characterized in that: The antibacterial finishing agent is prepared by the preparation process of the organosilicon antibacterial finishing agent according to any one of claims 1 to 6.
8. A method for using the organosilicon antibacterial finishing agent as claimed in claim 7, characterized in that: The natural fiber fabric is dipped and rolled in the organosilicon antibacterial finishing agent as claimed in claim 7 at a bath ratio of 3-4:1, double-dipping and double-rolling, the roller pressure is 0.05-0.1MPa, and the liquid rate is controlled to be 100%; the fabric is sent into the drum, the pressure in the drum bin is adjusted to 0.1-0.2MPa, maintained for 1-2min, centrifuged to remove the liquid for 1-3min, vacuum dried, washed with water, and fixed at a low temperature of 10-20°C.
Citation Information
Patent Citations
Antibiotic odourproof fiber
CN101067231A
Preparation method for antibacterial nanomaterial
CN105924688A
Nanoparticle fluid, antistatic PVC waterproof coiled material and preparation method
CN115895043A